FROM THE EDITOR = Redaksioneel - Lategan, Bernard C. (Scriptura, 1985)
Healthy human relations and the question of basic human rights are focal points of interest at a time when the HSRC is conducting a large-scale investigation into Intergroup Relations. The view of man underlying the various approaches seldom receives sufficient attention. A sound Biblical anthropology has much to contribute in this respect and the first article by Professor Suggit discusses some of these aspects, seen from a Biblical-theological perspective.